The Entertainment Strategies in Digital Content: A Uses and Gratifications Study on Going Seventeen Variety Show Program - Samatan, Nuriyati; Ginting, Selamat; Maryati, Maryati; Aladdin, Yuri Alfrin; Tyaga, Rianisa Shafira (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This study aims to analyze the variety show program as Variable X1, Content Quality (Variable X2), and Fulfillment of Entertainment Needs (Variable Y). The research object is the variety show program 'Going Seventeen' aired through the YouTube channel, analyzed through the Uses and Gratifications Theory. This research is quantitative, using a positivistic paradigm, with a non-probability sampling method, specifically purposive sampling. Determination of the sample size using the Slovin's formula, with the assumption that the number of followers is known, a margin of error of 0.5%, totaling 400 respondents. Findings: This study found a significant influence between the variety show program 'Going Seventeen' and content quality on the fulfillment of entertainment needs for Seventeen fans. Analysis through the Uses and Gratification Theory found that Going Seventeen can be accessed through the Going Seventeen YouTube channel, indicating that the variety show significantly influences the fulfillment of entertainment needs. Content quality (X2) also significantly affects variable Y, and simultaneous testing shows that the variety show program significantly influences variable Y.